A impossibilidade da prestação e suas consequências nas relações obrigacionais - Manfredi, Victor Augusto Aguiar (2025)
The objective of this research is to present the legal framework applicable to the impossibility of performance and its main consequences in the obligation relationship. This subject is relevant because, although the topic is of utmost importance, as it addresses a situation in which the contract is terminated through means other than performance, the Brazilian Civil Code and national legal literature have, in general, not sufficiently studied it, nor have they provided conclusive answers to various doubts and controversies related to it, including the effects produced by the different types of supervening impossibility. Given this gap, due to the cultural and legal proximity between the countries, the Portuguese literature and legislation, which are more advanced on the subject, will be used for this research to gather the necessary insights to answer the questions that will be raised throughout this work